PENGEMBANGAN BAHAN AJAR BERBASIS PROBLEM BASED LEARNIG (PBL) MATA PELAJARAN IPA PADA TEMA LINGKUNGAN SAHABAT KITA SISWA KELAS V SEKOLAH DASAR - Hidayat; Muhammad Amir; Herliani (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
Every education should experience a new innovation designed to teach special skills, beliefs and concepts to become better. The 2013 curriculum emphasizes performance assessments to determine the achievement of student competencies that include knowledge, skills and attitudes, the focus of educational assessments is the successful learning of learners to achieve the competencies defined in this case teachers can enrich ideas and ideas to help optimize student thinking skills. IPA Learning provides students to develop curiosity, knowledge, improve process skills, and awareness to appreciate the nature of God's creation and preserve the surrounding natural environment as well as the basis for continuing to a higher level of education.The main objective of Problem Based Learning (PBL) is the ability to think critical and problem solving skills while developing learners ' ability to actively build their own knowledge. The PBL is also intended to develop the independence of learning and the social skills of learners that are formed when they work to identify relevant information, strategies, and learning resources to resolve problems. The research method used is research and Development to produce a specific product, and to test the effectiveness of the product. Research and Development aims to improve the quality of education and develop and validate the outcomes of education. The study obtained pre-test and post-test value data which will be carried out by the process of data processing using SPSS 2.4 i.e. the T test in pairs (Paired-Samples T Test) wasobtained that the average value of Pre-Test 68.4 and the average Post-Test value of 87.8. Number of 15 students. Deviation Freedom 14 value sig. 2 tailled 0.000 with a degree of confidence 95%. Where the lowest grade pre-test students are 60 and the highest 75 while the lowest post-test students are 85 andthe highest 93. Based on the results it shows that the grades of students increased by 19.4% or 291 points. It can be said that the PBL model SCIENCE subject reference book developed can improve student learning outcomes.